2021
DOI: 10.1038/s41598-021-89002-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical biofilm disruption causes microbial and immunological shifts in periodontitis patients

Abstract: Periodontitis is characterized by subgingival biofilm dysbiosis, inflammation and tissue destruction. Current treatment involves mechanical biofilm disruption known as non-surgical periodontal therapy (NSPT). This study sought to characterise the impact of treatment on microbial diversity and overall community, and the parallel impact on host inflammation in the oral cavity. Fourty-two periodontitis patients were included in this study, with periodontal clinical parameters, subgingival plaque and saliva sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 70 publications
5
43
0
Order By: Relevance
“…The present analyses indicated that the subgingival microbiome correlated with the salivary levels of certain mediators in patients with periodontitis ( Figure 4 ) and in healthy subjects ( Supplementary Figure 4 ), an observation that should contribute to the understanding of the role of specific members of the microbial community and the disease. We have chosen to correlate the inflammatory mediator levels in saliva with microbiome data of a pool of subgingival sites, as recently performed [ 73 ] but differing from other studies [ 28 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present analyses indicated that the subgingival microbiome correlated with the salivary levels of certain mediators in patients with periodontitis ( Figure 4 ) and in healthy subjects ( Supplementary Figure 4 ), an observation that should contribute to the understanding of the role of specific members of the microbial community and the disease. We have chosen to correlate the inflammatory mediator levels in saliva with microbiome data of a pool of subgingival sites, as recently performed [ 73 ] but differing from other studies [ 28 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that R. aeria and H. parainfluenzae are beneficial to the host. On the other hand, a longitudinal study on periodontitis subjects submitted to periodontal treatment reported that the abundance of Rothia showed negative associations with Selenomonas, Fusobacterium , and Prevotella [ 73 ]. Thus, it is possible that Rothia and/or H. parainfluenzae did not directly trigger CCL2 production or inhibit the production of inflammatory mediators but would meet suitable conditions for growth under an environment where inflammation is resolved.…”
Section: Discussionmentioning
confidence: 99%
“…One theory is that microbial diversity is higher in the subgingival plaque of patients with periodontitis [ 37 , 38 ], which is attributed to the greater pocket depth affecting the availability of nutrients and/or the impairment of the immune system, allowing the growth of a more diverse microbial community. In line with this theory, Johnston et al detected a decrease in alpha diversity after nonsurgical periodontal treatment [ 20 ].…”
Section: Discussionmentioning
confidence: 94%
“…They identified a reduction in bacteria of the orange and red complexes and an increase in Actinomyces species after periodontal therapy. In initial studies applying a comprehensive approach, next-generation sequencing (NGS) was used to investigate complex subgingival microbial changes due to nonsurgical periodontal therapy but without comparing different therapies [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The salivary microbiota composition of six individuals was determined before and 4 h after nitrate intake. For analysis of the bacterial composition, R programming language (R Core Team, 2014) was used as described by Johnston et al (2021). In short, Wilcoxon sign rank (wilcox.test function) and Spearman's rho (cor.test function) tests were performed.…”
Section: Discussionmentioning
confidence: 99%